A Low-Cost Multimedia Robotic Platform for Dance Performances: D4NC3R Robot - Nogueira, Alan D. P.; S. Filho, Rinaldo T.; Ferreira, Francisco W. C.; S. Filho, Eduardo L.; Leal, Lucas De O.; Pereira, Leonardo M; Salles, Laurita; Burlamaqui, Aquiles M. F. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
The integration of technology creates opportunities for the use of robotics in artistic performances and works. However, due to high costs, access to this type of technology is limited. The goal of this article is to report on the development of the D4NC3R Robot, a low-cost multimedia robotics platform designed by the 10 Dimensães project, with the goal of democratizing access to robotics in art.